Comparative hybrid arrest by tandem antisense oligodeoxyribonucleotides or oligodeoxyribonucleoside methylphosphonates in a cell-free system. - Maher, L J (1988)
Antisense oligonucleotides containing either anionic diester or neutral methylphosphonate internucleoside linkages were prepared by automated synthesis, and were compared for their ability to arrest translation of human dihydrofolate reductase (DHFR) mRNA in a nuclease treated rabbit reticulocyte lysate. In the case of oligodeoxyribonucleotides, tandem targeting of three 14-mers resulted in synergistic and complete selective inhibition of DHFR synthesis at a total oligomer concentration of 25 microM. Hybrid arrest by three or six tandem oligodeoxyribonucleoside methylphosphonates was dramatically less effective. This difference does not result from preferential recognition of hybrids involving oligodeoxyribonucleotides by endogenous RNaseH activity. A ribonuclease protection assay demonstrated that antisense oligodeoxyribonucleoside methylphosphonates bind selectively to target RNA sequences, but with 275 fold lower affinity than the corresponding oligodeoxyribonucleotides. This low binding affinity results in poor arrest of translation, and may be related to the stereochemistry of the methylphosphonate linkage.